Do disturbed environments affect density of the tunnel-web spider Acanthogonatus centralis (Mygalomorphae: Nemesiidae) from native grasslands in Argentina? - Pompozzi, Gabriel Alejandro (2018)
Disturbance is an important factor affecting community composition and biodiversity in natural ecosystems. The Ventania hill system in central Argentina presents several ecosystem disturbances. Spiders are good candidates for studies related to human impact and conservation, as they can be good biological indicators of certain ecosystems. Therefore, we tried to elucidate if the abundance and spatial distribution of the mygalomorph spider Acanthogonatus centralis (Nemesiidae) are affected by different degrees of disturbance in these hilly grasslands. We studied 3 sites with different levels of disturbance located in the Ventania system in southwestern Buenos Aires Province, Argentina. We did not find differences in the mean density of A. centralis among sites. The highest density of this spider species was found in the site with the highest level of disturbance. In addition, the spatial arrangement indicated an aggregate distribution. In conclusion, we found that A. centralis populations are not affected by different levels of disturbances.